Problems with improvising faced by saxophone students in the Faculty of Music UiTM / Azzmer Azzmiruddin Nashuruddin - Nashuruddin, Azzmer Azzmiruddin (2014)
Music is a human best friend because music can fulfill their empty spaces in their daily life. For example, music is always played in a car, public transport, even at shopping complex, Music plays an important role in healthy life. Music can be used as therapy for the sick and disabled Research findings have found that music therapy is very useful for human life because “music therapy has decreased anxiety levels in many medical settings” (Clark, Isaacks, Wells, Frazier, Eek, Hepwonh & Chakravarthy. 2006. p. 247). Music is recognized as a combination 0f sounds and comprised of melody, harmony and rhythm. Other than that there is a spontaneous act in music performance which is called ‘improvisation’. Improvisation is a music composition that is created according to the composer’s or performer’s whim As stated by Tomassetti “when I hear great jazz soloists, I can appreciate that they are making beautiful music»improvised music that transcends the choice of notes and rhythms and communicates with the audience on many levels” (Tomassetti, 2003, p. 17). Other than that “improvisation has been an important part of music performance for thousands of years” (Rummel, 2010, p‘ 1).